Recreational drug-induced psychosis: a literature review (Research, Society and Development, 2021)
Psychosis is a broad term that characterizes a series of disorders that have in common the production of so-called psychotic symptoms, mainly delusions and hallucinations. Psychotic disorders can be divided into primary and secondary, including substance-induced psychotic disorders in this last category, among which recreational drugs stand out. The aim of this review was to analyze the main pathophysiological, symptomatic, diagnostic and therapeutic characteristics of psychotic disorders related to the use of recreational drugs. A search for previous works was carried out on the SciELO, Lilacs and PubMed platforms and a total of 27 scientific articles were included after application of inclusion and exclusion criteria. Through the studies analyzed, it was observed that the drugs most often associated with psychotic disorders were cannabis, amphetamines, alcohol and cocaine, with delusions, especially persecutory, and auditory hallucinations being the main reported symptoms. Although the pathophysiology of these disorders is not completely understood, there is evidence that the use of illicit drugs is a risk factor for the development of psychotic events, therefore, the knowledge of the factors involved in this relationship is important in clinical practice. In conclusion, it is important that health professionals know that the use of recreational drugs can lead to the development of psychosis and that they know how to assess the best way to approach these patients so that they can offer the best possible support.